Representasi Pesan Moral dalam Film Dokumenter ”Ngawitan Ngariksa Jagat” - Yoga Anggara; Haryadi Mujianto; Ismira Febrina (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
“Ngawitan Ngariksa Jagat” is a documentary genre film offering that shows the lives of the Sundanese Wiwitan harmonious community. This film is an orientation documentary genre in discussing the Sundanese Wiwitan perspective in general society and the perspective of the wider community. This research uses a descriptive qualitative approach with Roland Barthes' semiotic analysis method, which involves examining signs in videos at three levels: connotation (figurative meaning), denotation (actual meaning), and myth (history). Data is collected through documentation from relevant sources such as journals, books, films and websites. Primary data comes from observations of the film "Ngawitan Ngariksa Jagat" Instagram, while secondary data includes articles, journals and other documents. Researchers select and analyze relevant scenes to obtain moral meaning through semiotic analysis. The research results show that various aspects of Sundanese culture, such as religious rituals, music and traditional clothing, have deep meanings that reflect the harmonious relationship between humans and God and their ancestors. Meaning of Denotation and Connotation Every cultural element, from historical explanations to worship practices, contains deeper meaning. The myths that emerge in this practice emphasize the importance of sincerity, respect for ancestors, and awareness of cultural identity. This shows that cultural beliefs and values ​​play an important role in shaping people's behavior and attitudes.